STUDI PENGETAHUAN TENTANG POLA SWAMEDIKASI MASYARAKAT DALAM MENGATASI GEJALA BATUK DI PERUMAHAN ALLANDREW KECAMATAN MALALAYANG KOTA MANADO - Jeremy Mamonto; Weny Indayany Wiyono; Deby Afriani Mpila (PHARMACON, 2024)
Self-medication for cough symptoms is an act of treating all cough complaints/symptoms in oneself using simple medicines that are obtained without a doctor's advice. This research was conducted using a descriptive analytic survey method with a cross sectional design by distributing questionnaires to the Allandrew Housing community. The purpose of this study was to determine the level of public knowledge about self-medication for cough symptoms and to find out the pattern of self-medication in the Allandrew Housing community. Based on research on 92 respondents, it showed that 90.22% of respondents were in the good category regarding knowledge about what self-medication was, the level of knowledge with the category was lacking in knowing the difference between expectorant and intuitive drugs with a proportion of 45.65% and the good category in distinguishing the types of cough medicines consumed with the proportion of 73.91%. The pattern of self-medication in this study is that people directly buy drugs at pharmacies with a proportion of 51.09% and choose chemical drugs for self-medication with a proportion of 56.52%. Key words: Self-medication, Cough, Community.